Pressurised metered dose inhaler-spacer technique in young children improves with video instruction - Shaw, N.; Le Souëf, P.; Turkovic, L.; McCahon, L.; Kicic, Anthony; Sly, P.; Devadason, S.; Schultz, A. (Springer Berlin, 2016)
© 2016, Springer-Verlag Berlin Heidelberg. The importance of good device technique to maximise delivery of aerosolised medications is widely recognised. Pressurised metered dose inhaler (pMDI)-spacer technique was investigated in 122 children, aged 2–7 years, w ith asthma. Eight individual steps of device technique were evaluated before and after viewing an instructional video for correct device technique. Video measurements were repeated every three months for nine months. Device technique improved directly after video instruction at the baseline study visit (p < 0.001) but had no immediate effect at subsequent visits. Additionally, pMDI-spacer technique improved with successive visits over one year for the group overall as evidenced by increases in the proportion of children scoring maximal (p = 0.02) and near-maximal (p = 0.04) scores. Conclusion: Repeated video instruction over time improves inhaler technique in young children.What is Known:• Correct device technique is considered essential for sufficient delivery of inhaled medication.• Poor inhaler use is common in young asthmatic children using pressurised metered dose inhalers and spacers.What is New:• Video instruction could be used as a strategy to improve device technique in young children.